Aspects of landscape evolution, lineaments and fault zone mineralisation in southeast Ireland - Jordan, David (Trinity College (Dublin, Ireland). Department of Geology, 2008)
The findings of this work are presented in 8 chapters. Chapter 2 deals with a deep weathering profile in limestone at the Timahoe, County Kildare. Detailed analysis of materials collected from an investigatory borehole show that the weathering profile is a pocket deposit. It is proposed that weathering of a pyrite rich rock generated sulphuric acid that dissolved carbonate leaving behind an insoluble silica rich residuum. The Timahoe pocket deposit was initially mistaken for a buried palaeoriver due to its linearity, therefore other claimed palaeorivers in the region may also be pocket deposits. Furthermore, the practice of reconstructing the missing section above a pocket deposit to the Namurian level, for the purpose of landscape evolution studies, may be justified if the local Namurian rocks contain appreciable pyrite.
Keywords: Geology, Ph.D.; Ph.D. Trinity College Dublin